GP60 and SPARC as albumin receptors: key targeted sites for the delivery of antitumor drugs - Ji, Qingzhi; Zhu, Huimin; Qin, Yuting; Zhang, Ruiya; Wang, Lei; Zhang, Erhao; Zhou, Xiaorong; Meng, Run (Frontiers in Pharmacology, 2024)
Albumin is derived from human or animal blood, and its ability to bind to a large number of endogenous or exogenous biomolecules makes it an ideal drug-carrier. As a result, albumin-based drug delivery systems are increasingly being studied. With these in mind, detailed study of transport mechanism about albumin-based drug-carriers are particularly important. As albumin receptors, glycoprotein 60 (GP60) and secreted protein acidic and rich in cysteine (SPARC) play a crucial role in the delivery of albumin-based drug-carriers. GP60 is expressed on vascular endothelial cells and enables albumin to cross the vascular endothelial cell layer, and SPARC is overexpressed in many types of tumor cells, while it is minimally expressed in normal tissue cells. Thus, this review supplements the existing articles by detailing the research history and specific biological functions of GP60 or SPARC, and their research advances in the delivery of antitumor drugs using albumin as a carrier. Meanwhile, the deficiencies and future perspectives in the study of the interaction of albumin with GP60 and SPARC were also pointed out.